Preparative HSCCC isolation of phloroglucinolysis products from grape seed polymeric proanthocyanidins as new powerful antioxidants. (1st December 2015) - Zhang, Shuting; Cui, Yan; Li, Lingxi; Li, Yuanyuan; Zhou, Peiyu; Luo, Lanxin; Sun, Baoshan
Highlights: Polymeric proanthocyanidins were transformed into bioactive molecules by phloroglucinolysis. HSCCC method was developed to largely separate the phloroglucinolysis products. The strong antioxidant activity of catechin-derivatives was verified for the first time. Abstract: Polymeric proanthocyanidins isolated from a grape seed phenolic extract were hydrolysed in the presence of phloroglucinol into monomer catechins and their nucleophile derivatives. Each of the phloroglucinolysis products was successfully separated and isolated in large amount by semi-preparative HSCCC technique under the optimized conditions based on a selection of suitable solvent system. The optimized solvent system consisted of n -hexane–ethyl acetate–water (1:80:80, v/v/v) with a combination of head–tail and tail–head elution modes. By only one-step HSCCC separation, the purity of each obtained phloroglucinolysis product, including monomer catechins and their nucleophile derivatives was above 76%, verified by UPLC. The structures of these products were tentatively identified by UPLC based on their retention time and further confirmed by MS and 1 H NMR analysis. Furthermore, by DPPH, ABTS and FRAP assays, it was verified that all these phloroglucinolysis products possessed strong antioxidant activities, being catechin-nucleophile derivatives more powerful than free catechins.